SPLIT-FACE COMPARATIVE ANALYSIS OF MICRO-NEEDLING WITH TRANEXAMIC ACID VS VITAMIN C SERUM IN MELASMA - Raza, Musarrat Hussain; Iftikhar, Nadia; Anwar, Ayesha; Mashhood, Asher Ahmed; Tariq, Shahan; Hamid, Muhammad Ammar Bin (Journal of Ayub Medical College Abbottabad, 2022)
Background: Melasma is a very common skin problem that is much more prevalent in women. In our society, it results in many psycho-social implications and eventually leads to an impaired quality of life. Many treatment modalities have been developed for it. However, in recent years resistant forms of melasma have emerged that are unresponsive to the usual first line treatment options. Thus, this study is being conducted to explore new treatment modalities for this disease by using micro-needling with vitamin C and tranexamic acid. Methods: Thirty patients participated in this non-randomized clinical trial including 11 males and 19 females. All patients received Tranexamic acid via micro-needling on right side of the face and Vitamin C on the left side. A total of three biweekly sessions were performed. Patients’ response was evaluated at week 2, 4 and 6 on the basis of Physician Global Assessment, Patient Global Assessment, modified Melasma Area Severity Index and clinical assessment. Paired sample t-tests were used to calculate the difference in the means of two groups at 2, 4 and 6 weeks and p-value of <0.05 was considered significant. Results: After first session, there was more improvement observed with tranexamic acid. At the end of 6 weeks, modified Melasma Area Severity Index, Physician Global Assessment and Patient Global Assessment showed significant improvement with both tranexamic acid and vitamin C. However, the difference between them was not statistically significant (p>0.05). Conclusion: Both Tranexamic acid and Vitamin C are potent therapies for melasma as an adjuvant to micro-needling.